-13-7p=p-1+6

Simple and best practice solution for -13-7p=p-1+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13-7p=p-1+6 equation:


Simplifying
-13 + -7p = p + -1 + 6

Reorder the terms:
-13 + -7p = -1 + 6 + p

Combine like terms: -1 + 6 = 5
-13 + -7p = 5 + p

Solving
-13 + -7p = 5 + p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-1p' to each side of the equation.
-13 + -7p + -1p = 5 + p + -1p

Combine like terms: -7p + -1p = -8p
-13 + -8p = 5 + p + -1p

Combine like terms: p + -1p = 0
-13 + -8p = 5 + 0
-13 + -8p = 5

Add '13' to each side of the equation.
-13 + 13 + -8p = 5 + 13

Combine like terms: -13 + 13 = 0
0 + -8p = 5 + 13
-8p = 5 + 13

Combine like terms: 5 + 13 = 18
-8p = 18

Divide each side by '-8'.
p = -2.25

Simplifying
p = -2.25

See similar equations:

| 9-4(p-1)=5p+5 | | 1/4x-1/3=1/2 | | 2x/3-15=-23 | | 4x-5=-12x-229 | | 4-2(6x+1)=2x-2(2x+9) | | 11x-11=-33 | | d^2+4d+12=0 | | -36+2x=8x+8 | | 6y+19=2y-5 | | 5(x-4)-3=-2(x-3) | | (7x^2+22x-4)-(5x^2+3x-39)= | | (x-4)(x+8)(x-(2x+3i))(x-(2x-3i))=0 | | (x-3)-4=(x-5) | | 9+4(x+1)=11 | | w-2xy=2xz | | -2/3x=-5/9 | | 16(v+1)-4v=3(4v+3)-18 | | 4x+3=3x-15 | | 1000/x=19.3 | | 9+5(x+1)=11 | | 18-4x=-2(2x+6) | | 16-7x=-12 | | 2x(2x-7)=-12 | | 4*x=-19 | | -15-2x=16-(3x-y) | | 5r+6=4r-2(r-3) | | 1/2=3x=1/9 | | y+14.6=13.75 | | D^3=1932367.15findtheD | | 3/8-x=5/6 | | 14/39*3/4 | | -3(2x-9)=42 |

Equations solver categories